Vehicle-to-grid : a sociotechnical transition beyond electric mobility /: a sociotechnical transition beyond electric mobility. (2019) - Noel, Lance; Zarazua de Rubens, Gerardo; Kester, Johannes; Sovacool, Benjamin K
No abstract available